Strategic Roles of Motivational Factors in Inspiring Employees Commitment to Company - Narentheren a/l, Kaliappen (2011)
The hospitality industry playing vital role in tourism industry world wide and its employees play an important role in tendering the service to the potential customers. This study examines the strategic roles of motivation factors among the Berjaya Georgetown Hotel employees. This study focus on why employees choose to work in Berjaya Georgetown Hotel and determine the most significant motivational factor for Berjaya Georgetown Hotel employees. Besides that, this study also identifies differences between genders in term of preference towards the motivational factors. Finally, study about the relationship between motivational factors towards employee’s motivation. The researcher uses nine independent variables to test the relationship towards the employee’s motivation. Thus, the data was gathered through distributed questionnaires answered by 70 employees from Berjaya Georgetown Hotel. Data was analysed using SPSS v.11 where frequency distribution used to analyse demographic variables and descriptive statistics used to analysed motivational factors. Regression analysis was used to test the relationship between the motivational factors towards employee’s motivation. The results revealed that the main reason employee chose to work in Berjaya Georgetown Hotel was based on ‘salary’, ‘fringe benefit’ and ‘interesting job’. Research finding revealed that the most significant motivational factors were first ‘salary’, second ‘opportunities for advancement’ and third ‘fringe benefits’. Data revealed that the male employees in Berjaya Georgetown Hotel preferred ‘salary’ as first choice but the female employee’s preferred ‘working environment’ as their significant motivational factor. The findings also show that there was positive relationship between nine motivational factors towards the employee’s motivation.